Cuantificación de flavonoides totales y taninos presentes en el decocto e infuso de hojas de thea sinensis l. “té” verde y negro” - Acevedo Chuñuca, Elizabeth (2011)
The present research was designed to spectrophotometric quantification of total flavonoids and tannins sinensis L. Tea "Green Tea". Green Tea boxes were purchased in the enclosure Trujillo. The quantification of total flavonoids was performed by the method described by Kostennikova Z. adapted by the department of Pharmacognosy, Faculty of Pharmacy and Biochemistry of the UNT and expressed as mg of quercetin / g of Thea sinensis L. It was found that the highest percentage to decoct green tea 1.6%, and the lowest percentage was 1.12% in black tea infused. The quantification of tannins was determined by spectrophotometry using the method Tungsten-molybdic-phosphoric adapted by the department of Pharmacognosy, Faculty of Pharmacy and Biochemistry of the UNT, found that the highest percentage of black tea to decoct with 21.68% and the lowest percentage was 0.23% in the infused green tea. The results were evaluated by t-student test, using a significance level of 95% (P <0.05), it was determined that there are significant differences